2020
DOI: 10.3390/pathogens9070526
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Resistance and Changes in Distribution of Serotypes of Streptococcus agalactiae in Poland

Abstract: Streptococcus agalactiae is responsible for serious infections in newborn babies, pregnant women, and other patients. The aim of this study was to evaluate antimicrobial susceptibility, serotype distribution, and virulence determinants of the S. agalactiae isolates derived from clinical specimens considering the global increase of both antibiotic resistance and virulence. A total of 165 isolates were identified and serotyped by PCR techniques. Antimicrobial susceptibility was assessed by disk diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…CGE, SP80, and all fractions ( 25 ) were evaluated for antimicrobial activity against S. agalactiae ATCC 12386, and the microbial growth was measured by monitoring the increase in optical density at 595 nm (OD 595 ) using a Victor3 1420 multilabel counter plate reader (Perkin Elmer, Waltham, MA, USA). The values are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CGE, SP80, and all fractions ( 25 ) were evaluated for antimicrobial activity against S. agalactiae ATCC 12386, and the microbial growth was measured by monitoring the increase in optical density at 595 nm (OD 595 ) using a Victor3 1420 multilabel counter plate reader (Perkin Elmer, Waltham, MA, USA). The values are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Velázquez et al ( 46 ) analyzed 96 strains of S. agalactiae , all of which were sensitive to penicillin G at an MIC ranging from 0.012 to 0.094 μg/ml, results corroborated by the current study findings. Kaminska et al ( 25 ) analyzed 165 strains of clinical isolates of S. agalactiae and all were sensitive to penicillin G, with an MIC ranging from 0.032 to 0.125 μg/ml. These studies are corroborated by the findings of the present work, which observed an MIC of 0.038 μg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…However, the proportion of serotype III isolated in Thailand was higher than the proportions reported from those three counties (China 32.2%, Belgium 21.0%, and France 25.7%). In contrast, serotype V was the most frequently identified serotype in Poland, Norway, Sweden, Australia, and New Zealand ( Bergseng et al, 2008 ; Zhao et al, 2008 ; Gudjónsdóttir et al, 2015 ; Kaminska et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, serotype V was the most frequently identified serotype in Poland, Norway, Sweden, Australia, and New Zealand (Bergseng et al, 2008;Zhao et al, 2008;Gudjónsdóttir et al, 2015;Kaminska et al, 2020). The observed increase in the prevalence of non-serotype III was further investigated for a factor related to the mechanism of change in virulence via virulence gene detection.…”
Section: Discussionmentioning
confidence: 99%
“…Worrying issues are the increasing incidence of antibiotic resistance among GBS, such as to penicillin G or macrolides, which are first-line therapies. In our study, we chose the most frequently represented capsular serotypes in Poland, which are IA, III, and V [ 2 ]. These serotypes are also the most common cause of urinary tract infections among adults [ 3 ].…”
Section: Introductionmentioning
confidence: 99%